GRAMMATICAL COMPETENCE AND ITS ROLE IN LANGUAGE TEACHING - Abdishukur Musaevich Shofkorov (Modern American Journals, 2025)
The article attempts to shed light on grammatical competence and its role in language teaching. It also discusses the use of neuropedagogical technologies in language learning.
Keywords: language, language teaching, competence, language competence, grammar, grammatical competence, neuropedagogy, neuropedagogical technology.